2017
DOI: 10.1088/1361-665x/aa87d6
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of magnetorheological damper with hysteresis division

Abstract: Due to the complex nonlinearity of magnetorheological (MR) behavior, the modeling of MR dampers is a challenge. A simple and effective model of MR damper remains a work in progress. A novel model of MR damper is proposed with force-velocity hysteresis division method in this study. A typical hysteresis loop of MR damper can be simply divided into two novel curves with the division idea. One is the backbone curve and the other is the branch curve. The exponential-family functions which capturing the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Coincidentally, the associated velocities in this area are relatively small, and the hysteresis displays more distinctly in the force-velocity plot. However, from a view of rate-independence of hysteresis (Visintin, 2013;Chen et al, 2018), the experimental results (Wang and Liao, 2011;Bai et al, 2015;Sapinski et al, 2017;Yu et al, 2017;Shou et al, 2018) show that the hysteresis behaviors of MR fluids occur in force-displacement plot while not in the typical force-velocity plot. The "rate-independence" concept is defined by the path of the couple [with the input z(t) and the output F(t) of the system] that is invariant with respect to any increasing time, i.e., the output is not dependent on the derivative of the input z (Visintin, 2013).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Coincidentally, the associated velocities in this area are relatively small, and the hysteresis displays more distinctly in the force-velocity plot. However, from a view of rate-independence of hysteresis (Visintin, 2013;Chen et al, 2018), the experimental results (Wang and Liao, 2011;Bai et al, 2015;Sapinski et al, 2017;Yu et al, 2017;Shou et al, 2018) show that the hysteresis behaviors of MR fluids occur in force-displacement plot while not in the typical force-velocity plot. The "rate-independence" concept is defined by the path of the couple [with the input z(t) and the output F(t) of the system] that is invariant with respect to any increasing time, i.e., the output is not dependent on the derivative of the input z (Visintin, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…At present, the research on MR hysteresis characteristics mainly focuses on the mechanical properties of MR actuators (Wang and Liao, 2011;Bai et al, 2013Bai et al, , 2015Sapinski et al, 2017;Yu et al, 2017;Chen et al, 2018;Shou et al, 2018), such as MR dampers and MR clutches/brakes. Experimental tests of MR dampers in valve or shear mode show that the hysteresis only occurs around the direction-change points under sinusoidal displacement excitations (Wang and Liao, 2011;Bai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To predict the non-linear hysteresis loops, the dynamic models should be established (Guo and Hu, 2005;Ikhouane and Dyke, 2007;Yu et al, 2017). A typical construction of the parametric model shown in Equation (1) is used in this study.…”
Section: Modeling and Identificationmentioning
confidence: 99%
“…To verify the accuracy of the proposed model, a conventional model is selected for performance comparisons. The mathematical function of the conventional model is shown in Equation 5 (Yu et al, 2017).…”
Section: Modeling and Identificationmentioning
confidence: 99%
“…Lumped parameter models have been the main tool for modeling of MR dampers because of their simplicity. They are comprehensively reviewed in works (Sahin et al, 2010;Wang and Liao, 2011), and more recent works can be found in Yu et al (2017) and (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%